Spectra of some selfadjoint Jacobi operators in the double root case - Motyka, Wojciech (My University, 2015)
In this paper we prove a mixed spectrum of Jacobi operators defined by $\lambda_n=s(n)(1+x(n))$ and $q_n=-2s(n)(1+y(n))$, where $(s(n))$ is a real unbounded sequence, $(x(n))$ and $(y(n))$ are some perturbations.
Opuscula Mathematica
Keywords: Jacobi matrices; double root case; asymptotic behavior; subordination theory; absolutely continuous spectrum; discrete spectrum